Anisotropic field dependence of the electronic transport in superconducting FeSe thin films. (4th June 2020) - Schneider, R; Zaitsev, A G; Fuchs, D; Hott, R
Abstract: Electronic transport measurements were carried out on c -axis oriented epitaxial FeSe thin films in static magnetic fields up to 14 T parallel to the crystallographic c -axis and parallel to the ab -plane. The temperature dependence of the upper critical fields B c 2 c and B c 2 a b was determined from the field dependence of the resistivity. While B c 2 c was orbitally limited, the larger B c 2 a b was paramagnetically limited. The anisotropy γ B was decreasing with decreasing temperature and revealed a pseudoisotropic behaviour towards zero temperature. This temperature dependence is indicative of the multiband character of FeSe. From measurements of the temperature- and field-dependent critical current densities the effective depinning or irreversibility field B c 2 ∗ was obtained, and its angular dependence yielded the effective mass anisotropy γ m . The temperature dependence of γ m, which was different from that of γ B, can be considered as another signature of multiband FeSe.